2022
DOI: 10.3390/app12063015
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the Consumption of Sugar-Sweetened Beverages and Metabolic Syndrome Components in Young Rural Adults in South Africa

Abstract: Background: Metabolic syndrome (MetS) is the key risk factor for cardiovascular disease (CVD) development. However, lifestyle habits including high consumption of sugar-sweetened beverages (SSBs) contribute to its onset. The current study was aimed at investigating the association between SSBs consumption and MetS components among young adults aged 22 to 30 years. Methods: This was a cross-sectional study where a total of 596 young adults (307 females and 287 males) participated. Blood pressure, biochemical as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Regarding sex, women have a higher tendency for weight and abdominal obesity and SM in most African studies [5,14,15,19,21,22]. This was noted in our series.…”
Section: Relationship Ms Gender and Agesupporting
confidence: 75%
See 1 more Smart Citation
“…Regarding sex, women have a higher tendency for weight and abdominal obesity and SM in most African studies [5,14,15,19,21,22]. This was noted in our series.…”
Section: Relationship Ms Gender and Agesupporting
confidence: 75%
“…As with hypertension and obesity, the incidence of MS increases with age [21]. In adolescents and children, a high incidence is mainly associated with lifestyle and dietary habits, increasing the prevalence of obesity and glucose intolerance [22].…”
Section: Relationship Ms Gender and Agementioning
confidence: 99%
“…Weight and height were assessed using the standard scale and ruler ( 33 ). Body mass index (BMI) was calculated as weight ( 35 ) divided by height (square in meter), then classified into normal weight (BMI: 18.5–24.9 kg/m 2 ), underweight (BMI < 18.5 kg/m 2 ), overweight (BMI: 25–29.9 kg/m 2 ), and obese (BMI ≥ 30 kg/m 2 ) ( 36 ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the Health Workers Cohort Study in the Mexican states of Morelos and Mexico reported that subjects consuming >2 servings of sweetened beverages daily are at 2.1 times greater risk of raised fasting plasma GLC compared with non-consumers [42]. Likewise, a cross-sectional study among young rural adults in South Africa found that the consumption of SSBs is significantly associated with increased high risk of high GLC [43].…”
Section: Discussionmentioning
confidence: 99%